Transport modes and tourism seasonality in Italy: By air or by road?. Issue 3 (May 2022) - Vergori, Anna Serena; Arima, Serena
From the late 1990s, the European air transport deregulation has led to the increasing use of the plane to reach tourist destinations. This article investigates the impact of tourists' changed traveling habits on Italy's seasonal tourism demand pattern. The role of transportation on seasonality, indeed, has been almost neglected in empirical research. We analyze international monthly arrivals by transport modes from 1997 to 2018, and we use the Gini index as a measure of seasonality. The Gini's decomposition allows us to evaluate the effects of the growth in the use of each transport mode (cars, planes, ships, trains) on seasonality. A beta regression model confirms that an increment in the proportion of tourist arrivals by airplane determines a reduction in Italy's overall seasonality of international tourism demand. These results might be a starting point for policy makers in developing strategies to counteract seasonality.